PENGARUH BRAND AMBASSADOR, DIGITAL MARKETING DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK EMINA PADA MAHASISWA UNIVERSITAS NEGERI PADANG - Sovia Octaviana; Rose Rahmidani (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to was conducted to determine the influence of Brand Ambassadors, Digital Marketing and Electronic Word of Mouth on Purchasing Decisions for Emina Cosmetic Products for Padang State University Students. The type of research used is causative research with a quantitative approach. The number of samples in this study were 100 Padang State University students, using purposive sampling technique. The data collection technique was carried out using a questionnaire with a Likert scale. This instrument has passed the validity and reliability tests, using the multiple linear regression analysis method with SPSS version 22 which has passed the classical assumption prerequisite test, namely the normality test, multicollinearity test and heteroscedasticity test, the hypothesis is then tested using the f-test, t-test, and coefficient of determination. The results of this study indicate that (1) Brand Ambassadors have a significant influence on Purchasing Decisions, (2) Digital Marketing has a significant influence on Purchasing Decisions, (3) E-WOM has proven significant to purchasing decisions, (4) Brand Ambassadors,Digital Marketing and Electronic word of mouth (E-WOM) have a significant influence on purchasing decisions